PERAN TOKOH AGAMA DALAM MEMINIMALISIR DEKADENSI MORAL REMAJA - Tri Mulya Budi Ongkai; Syarnubi Syarnubi; Irja Putra Pratama; Halimatussakdiah Halimatussakdiah; Padli Padli (PAI RAFAH, 2023)
Religious leaders as central in balancing society certainly have an active role in preventing the occurrence of adolescent moral decadence. Teenagers in their search do not mean many things that must be addressed, so they really need a good motivation or self-control figure in society. This research was conducted in Belatung Village, Lubuk Batang District, with data sources from village youth, religious leaders, and also the government. Data collection was carried out directly in the field through interviews, documentation, and observation. In solving adolescent problems, many people involve the community, especially the village religious apparatus. Juvenile delinquency in Belatung Village is classified as social delinquency such as drinking, stealing, illegal racing, and so on. Ketib's efforts in educating the morals or morals of the people in the maggot area are only focused on the world of education that is carried out, and which is his responsibility. The things that the ketib do include teaching the Koran which is carried out only at certain times, religious tausiah which is carried out in commemoration of Islamic holidays, and weekly yasinan which is followed by the community